Insights into group-specific pattern of secondary metabolite gene cluster in Burkholderia genus - Kim, Byeollee; Han, So-Ra; Lee, Hyun; Oh, Tae-Jin (Frontiers in Microbiology, 2024)
Burkholderia is a versatile strain that has expanded into several genera. It has been steadily reported that the genome features of Burkholderia exhibit activities ranging from plant growth promotion to pathogenicity across various isolation areas. The objective of this study was to investigate the secondary metabolite patterns of 366 Burkholderia species through comparative genomics. Samples were selected based on assembly quality assessment and similarity below 80% in average nucleotide identity. Duplicate samples were excluded. Samples were divided into two groups using FastANI analysis. Group A included B. pseudomallei complex. Group B included B. cepacia complex. The limitations of MLST were proposed. The detection of genes was performed, including environmental and virulence-related genes. In the pan-genome analysis, each complex possessed a similar pattern of cluster for orthologous groups. Group A (n = 185) had 14,066 cloud genes, 2,465 shell genes, 682 soft-core genes, and 2,553 strict-core genes. Group B (n = 181) had 39,867 cloud genes, 4,986 shell genes, 324 soft-core genes, 222 core genes, and 2,949 strict-core genes. AntiSMASH was employed to analyze the biosynthetic gene cluster (BGC). The results were then utilized for network analysis using BiG-SCAPE and CORASON. Principal component analysis was conducted and a table was constructed using the results obtained from antiSMASH. The results were divided into Group A and Group B. We expected the various species to show similar patterns of secondary metabolite gene clusters. For in-depth analysis, a network analysis of secondary metabolite gene clusters was conducted, exemplified by BiG-SCAPE analysis. Depending on the species and complex, Burkholderia possessed several kinds of siderophore. Among them, ornibactin was possessed in most Burkholderia and was clustered into 4,062 clans. There was a similar pattern of gene clusters depending on the species. NRPS_04014 belonged to siderophore BGCs including ornibactin and indigoidine. However, it was observed that each family included a similar species. This suggests that, besides siderophores being species-specific, the ornibactin gene cluster itself might also be species-specific. The results suggest that siderophores are associated with environmental adaptation, possessing a similar pattern of siderophore gene clusters among species, which could provide another perspective on species-specific environmental adaptation mechanisms.